The rubadub mystery - Blyton, Enid; Rowe, Eric (Nottinghemshire award publications limited, 2009)
When Miss Pepper takes the children to stay at a village inn by the sea she's hoping for a quiet holiday. But strange things happen at the inn and then an explosion at a nearby submarine base starts a police investigation. The children are determined to find the answers."